2020
DOI: 10.1007/s10518-020-00977-y
|View full text |Cite
|
Sign up to set email alerts
|

Behavior factor of concrete portal frames with dissipative devices based on carbon-wrapped steel tubes

Abstract: The key element characterizing the seismic vulnerability of existing prefabricated RC structures, not designed for earthquake actions, are friction-based connections between structural members; mainly those between beams and columns and beams and roofing beams. The paper discusses the effectiveness of dissipative connectors made of carbon wrapped steel tubes. In particular, it presents the results of Incremental Dynamic Analyses on portal frames, aimed at evaluating behavior factor values to be used in design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…10, showing the variability of q for the seven accelerograms adopted, for each model. On average, the variability of q is consistent with the values observed for the precast buildings analyzed in Pollini et al [32].…”
Section: Behavior Factor Estimationsupporting
confidence: 89%
See 2 more Smart Citations
“…10, showing the variability of q for the seven accelerograms adopted, for each model. On average, the variability of q is consistent with the values observed for the precast buildings analyzed in Pollini et al [32].…”
Section: Behavior Factor Estimationsupporting
confidence: 89%
“…The dissipative fuse devices based on CWSTs [31,32] considered in the present paper have two main purposes: (i) to connect beam-column joints in order to prevent the possible unseating failure of beams, and (ii) to act as dissipative fuses, thus reducing the effects of seismic actions on structural elements. Specific studies in automotive engineering on structural crashworthiness [33,34] showed that metals, combined with composite materials in thin-walled circular tubes, have excellent capacities of energy absorption under axial compressive loads.…”
Section: Cwst Dissipative Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the last reason, a crescent-moon-shaped device has been selected (Palermo et al, 2015;Hsu and Halim, 2017). It is interesting to note that other types of devices have been recently applied at the beam-to-column joints, such as the friction devices reported in the FREEDAM project (Santos et al, 2019;Francavilla et al, 2020) and the carbon-wrapped steel tubes reported in Pollini et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…The seismic displacement demand of the considered building typology could be reduced by placing additional mechanical devices at the beam-to-column joint for both new and existing buildings (Martinez Rueda 2002;Martinelli and Mulas 2010;Plumier 2007;Belleri et al 2017b;Pollini et al 2020;Francavilla et al 2020;Bressanelli et al 2021). The provision of additional devices is compatible with the dry-assembly construction system, being the devices put in place at the end of the erection sequence.…”
Section: Introductionmentioning
confidence: 99%